2017
DOI: 10.1098/rspb.2017.1248
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stress hormones and aggression on cooperative behaviour in subordinate meerkats

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms varied between cooperative activities as well as between the sexes. Subordinates of both sexes that were treated with a glucocorticoid receptor antagonist (mifepristone) exhibited significantly more pup protection behaviour ('babysitting') compared to those treated with glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 67 publications
3
37
1
Order By: Relevance
“…For example, in both African striped mice (Raynaud & Schradin, 2015) and meerkats (Carlson, Manser, et al, 2006;Dantzer, Braga Goncalves, et al, 2017), elevated HPA-axis activity increased alloparental behavior in males but not females, though in meerkats these effects depended upon the type of alloparental care behavior under consideration Dantzer, Braga Goncalves, et al, 2017;Santema, Teitel, Manser, Bennett, & Clutton-Brock, 2013). Two studies used an experimental approach in meerkats to show that elevated HPA-axis activity in subordinate females decreased their expression of two types of alloparental care behaviors (Dantzer, Braga Goncalves, et al, 2017) but increased the amount of time they spent close to pups (Santema et al, 2013). Subordinate male meerkats with experimentally elevated HPA-axis activity exhibited less pup-guarding behavior (babysitting) but more food provisioning (pup feeding: Dantzer, Braga Goncalves, et al, 2017).…”
Section: Evidence For the Effect Of Gcs On Alloparental Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in both African striped mice (Raynaud & Schradin, 2015) and meerkats (Carlson, Manser, et al, 2006;Dantzer, Braga Goncalves, et al, 2017), elevated HPA-axis activity increased alloparental behavior in males but not females, though in meerkats these effects depended upon the type of alloparental care behavior under consideration Dantzer, Braga Goncalves, et al, 2017;Santema, Teitel, Manser, Bennett, & Clutton-Brock, 2013). Two studies used an experimental approach in meerkats to show that elevated HPA-axis activity in subordinate females decreased their expression of two types of alloparental care behaviors (Dantzer, Braga Goncalves, et al, 2017) but increased the amount of time they spent close to pups (Santema et al, 2013). Subordinate male meerkats with experimentally elevated HPA-axis activity exhibited less pup-guarding behavior (babysitting) but more food provisioning (pup feeding: Dantzer, Braga Goncalves, et al, 2017).…”
Section: Evidence For the Effect Of Gcs On Alloparental Behaviormentioning
confidence: 99%
“…Two studies used an experimental approach in meerkats to show that elevated HPA-axis activity in subordinate females decreased their expression of two types of alloparental care behaviors (Dantzer, Braga Goncalves, et al, 2017) but increased the amount of time they spent close to pups (Santema et al, 2013). Subordinate male meerkats with experimentally elevated HPA-axis activity exhibited less pup-guarding behavior (babysitting) but more food provisioning (pup feeding: Dantzer, Braga Goncalves, et al, 2017).…”
Section: Evidence For the Effect Of Gcs On Alloparental Behaviormentioning
confidence: 99%
“…For example, Torres-Medina et al (2018) showed that silastic implants, time release pellets, or osmotic pumps that contain corticosterone can also suppress the responsiveness of the HPA axis in birds, which could decrease overall exposure to circulating corticosterone. Our study shows that even regular provisioning of exogenous GCs rather than implants, such as through food in our study (see also Dantzer et al, 2017) or through other methods (Vitousek et al 2018), may also decrease the activity of the HPA axis and cause a reduced ability to mount an increase in circulating GCs in response to an environmental challenge.…”
Section: Discussionmentioning
confidence: 68%
“…We visited sleeping burrows containing pups every day in the morning and recorded the identity of the attending babysitters. As we have done previously [32,35,38,41], we calculated relative babysitting contributions of each individual meerkat for each litter by dividing the total number of days an individual babysat a litter by the total number of days that this specific litter had a babysitter. Pup feeding behaviour for each pup produced by the dominant females in the different treatment groups was estimated using ad libitum Table 1.…”
Section: (D) Quantifying Cooperative Behaviour Of Offspringmentioning
confidence: 99%
“…We assessed how the treatments affected the relative babysitting and pup feeding contributions of subordinates when they were more than six months old (as they rarely do alloparental care behaviour when less than six months old [35]) from cortisol-treated, control and untreated mothers. Relative babysitting and pup feeding contributions are defined as the proportion of babysitting or pup feeding contributions exhibited by a specific individual compared to the total number of babysitting or pup feeding contributions for that litter exhibited by all individuals in the group that were more than six months of age at the time of the birth of the litter [35,38,41]. In these GLMMs (binomial errors), we included a three-way interaction between treatment, sex and age of the subordinate to assess if the effects of the treatments on babysitting or pup feeding varied according to the sex or age of the subordinate, as contributions to cooperative behaviour in meerkats are known to vary according to subordinate sex and age [35].…”
Section: (G) Statistical Analysesmentioning
confidence: 99%